Untangling electronic, optical and bonding properties of hexagonal bismuth borate SrBi2B2O7 crystal for ultraviolet opto-electronic applications: An ab initio study - Stambouli, Naouel Boudghene; Ouahrani, Tarik; Badawi, Michael; Reshak, Ali H.; Azizi, Sihem (Elsevier, 2019)
To realize the efficient frequency conversion, the nonlinear ultraviolet crystal must exhibit strong second harmonic generation and possible phase-matching condition. The current first principles calculations predict that SrBi2B2O7 represents potentially a new class of materials with such characteristics. For this aim, we present the first analysis of dynamical, bonding, linear and nonlinear optical properties of the SrBi2B2O7 single crystal. To untangle such properties, both density functional theory calculation and topological analysis were used. It is found that the compound exhibits a wide indirect band gap and an interesting bonding motif. In particular, the distortion caused by the stereochemically active lone pair of the s-state in the Bi3+ unit favors the enhancement of local dipole moment. In addition, the refraction index, absorption spectrum, phase matching and second harmonic properties were calculated and analyzed. According to the results, SrBi2B2O7 has a large d33 s-order susceptibility component which makes it a very promising UV nonlinear optical material. © 2019 Elsevier B.V.